Customers’ behavior intension regarding online shopping of general product and insecticide in Thailand - DINESH ELANGO; KRITCHANUT PRAYOONPONG (Fakultas Ekonomi, Universitas Bangka Belitung, 2020)
The global market of insecticide products is expected to garner around 16.7 Billion US by 2020, registering a CAGR of 5.0% during the forecast period 2014 to 2020. Companies are operating in this market focus on product launches as part of their growth strategy. As the retail sales of global e-commerce have continuously grown, e-commerce has gained the large share from physical retail over the last decade derived from the impact of greater internet access and technology development that make online shopping easier and more convenience. The research analyzes data of customer behavior intention by parallel compare impact of the data from general product and insecticide product. In analyzing data, single Linear Regression and multiple linear regression were employed to investigate the impact and difference between dependent and independent variable. The 400 respondents who are using online application and have online shopping experience were implied to investigate the factors that have intention to decision on purchase product via online channel in this research. The results have been interpreted that people have more concern on purchase of insecticide online in product attitude, customer service, purchase and delivery, and promotion of insecticide. This study concept and valid the customer behavior toward insecticide product for set strategy of the insecticide in online market.